BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN STRESS KERJA PADA TENAGA KESEHATAN DI FASILITAS KESEHATAN - Millati, Rida'; Dwijayanto, I Made Rio; Putra, Ryryn Suryaman Prana; Astuti, Yuni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Puskesmas have various tasks and work programs that are quite complex in their working areas. These tasks involve various aspects of health services, ranging from disease prevention, health promotion, to treatment for various community groups. Based on a preliminary study conducted at five Puskesmas located in Ciputat Sub-district, South Tangerang City, namely Puskesmas Kampung Sawah, Puskesmas Ciputat, Puskesmas Sawah Baru, Puskesmas Situ Gintung, and Puskesmas Jombang, through interviews with several health workers, it was revealed that they feel fully responsible for all the work received at the Puskesmas. Each health worker at the health center also has to deal with quite a lot of additional tasks, which often exceed the capacity of their main job. This indicates an excessive workload, which leads to high work stress. The purpose of this study was to determine several factors associated with work stress in health workers in health facilities. The research design used in this study was cross sectional. The study was conducted in the Ciputat District Working Area of South Tangerang City which consists of five Puskesmas, namely Puskesmas Kampung Sawah, Puskesmas Ciputat, Puskesmas Sawah Baru, Puskesmas Situ Gintung, and Puskesmas Jombang. The research was conducted in June 2023. The population in this study were all health workers at the Puskesmas of Ciputat District, South Tangerang City, totaling 82 people. The research sample amounted to 82 people who were selected using total sampling. The research instrument used a research questionnaire. Data analysis was conducted univariate and bivariate. The results showed an association between leadership style (p value: 0.022) and interpersonal relationships (p value: 0.036) on the incidence of stress. It is recommended to the health center to be able to apply a good leadership style to every employee of the health center, especially health workers by providing equal work and fair behavior towards health workers in order to prevent the onset of work stress in health workers and can improve good interpersonal relationships among coworkers and health workers in order to create harmony and a sense of harmony at work and minimize the occurrence of work stress in the work environment.Keywords: Leadership Style, Interpersonal Relationships, Stress.